2015
DOI: 10.3928/01477447-20150804-53
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Cost-Utility Analyses in Orthopedic Trauma

Abstract: As health care in the United States transitions toward a value-based model, there is increasing interest in applying cost-effectiveness analysis within orthopedic surgery. Orthopedic trauma care has traditionally underemphasized economic analysis. The goals of this review were to identify US-based cost-utility analysis in orthopedic trauma, to assess the quality of the available evidence, and to identify cost-effective strategies within orthopedic trauma. Based on a review of 971 abstracts, 8 US-based cost-uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Reviews within the subspecialties of sports medicine 2 and trauma 3 have found the quality to be strong, with QHES averages of 81.8 and 79.25, respectively. Brauer and colleagues have noted more orthopaedic studies complying with the recommendations of the First Panel after 1998 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviews within the subspecialties of sports medicine 2 and trauma 3 have found the quality to be strong, with QHES averages of 81.8 and 79.25, respectively. Brauer and colleagues have noted more orthopaedic studies complying with the recommendations of the First Panel after 1998 5 .…”
Section: Discussionmentioning
confidence: 99%
“…In the field of orthopaedics, prior systematic reviews have assessed the quality of CEAs across sports 2 and trauma 3 , finding the overall quality of studies to be good in these orthopaedic subspecialties. However, there has been no systematic examination of CEAs in upper extremity surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a review of the pharmacoeconomic evaluations for the use of Levodopa in Parkinson's disease was carried out, based on the QHES instrument [22], which qualifies methodological quality and has been used by other authors previously [45][46][47][48][49].Only the articles that met inclusion criteria and were considered of cost-utility were taken, finding that the five articles analyzed obtained an overall average score of 77.2 out of 100. This reflects that these studies are of good quality, and this is probably attributable to the fact that they were recently carried out following the current guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Since the introduction and application of the QHES instrument, the reported mean and median scores have been between 80 and 90. Therefore, the authors considered a QHES score of greater than 85 as an indicator of high quality [31][32][33][34].…”
Section: Quality Assessmentmentioning
confidence: 99%